Nagios Core Optimization By Utilizing Telegram as Notification of Disturbance - Fahreza Fahreza; Muhammad Rifqi (Journal of Applied Science, Engineering, Technology, and Education, 2020)
Network Monitoring System (NMS) is a system that is highly demanded internet service provider industry in this fast-developing information technology era. The availability of NMS is the best option to restore the service level agreement as a means to compete with other internet service providers’ competitors. The occurrence of disturbance in the network is often unnoticed by the network administrator. This may lead to a crucial problem in decreasing network quality as the impact of time-consuming in solving the problem. Through the explanation, the writer tried to anticipate by classifying problems using Pareto and integrated Nagios with Telegram Messenger as a notification of disturbance. Nagios has many features such as reports, event handlers, monitoring resources (CPU load, memory usage, status up / down, uptime, data traffic, bandwidth), etc. One notable feature owned by Nagios is blast notification of disturbance. It is a feature that will function when one of the devices is in trouble. This feature will inform the network administrator or authorized person in certain divisions as regards the error network. In this case, the problematic device can be categorized according to the parameters made by the network administrator.